Aspectos produtivos da gliricídia em diferentes densidades de cultivo e avaliação nutricional de silagens de gliricídia com diferentes proporções de milho - Castro Filho, Edivilson Silva (2014)
Gliricidia sepium (Jacq.) Walp. is a legume tree well adapted to water stress, with high levels of protein in their leaves making it a low-cost strategy for ruminants feeding during drought periods. In northeastern Brazil, gliricídia has been used as food for cattle and sheep in silvipastoral systems as well as silage or hay. It produces high dry matter yields of good nutritional quality being well accepted by the animals. The present study carried out at the Pedro Arle Experimental Station of Embrapa Coastal Tablelands in Frei Paulo County Sergipe, Brazil, was split on two trials. In the first one the aim was to evaluate the effect of different gliricidia crop densities over the biomass productive and qualitative parameters. The effect of the crop densities of 10,000; 20,000; 30,000, and 40,000 plants/ha was tested over the green biomass yields, dry matter yields, and on the levels of crude protein (CP), neutral detergent fiber (NDF), and acid detergent fiber (ADF) in leaves plus fine stems of gliricídia. A randomized block design with four replications was used. Fresh biomass production of leaves and stems, dry matter production of leaves, percentage of fresh leaves related to total fresh biomass, dry matter percentage in leaves of 13 cuts were evaluated during the growth period between 02/09/2009 and 18/12/2013. The productions of total fresh biomass, leaves fresh biomass, and leaves dry matter increased (P < 0,05) with higher densities of planting 20,000 plants/ha. Year effect (P < 0.05) was found only for total fresh biomass production, fresh leaves yield, percentage of fresh leaf biomass, leave dry matter content, and CP. It is recommended the density of 30000 plants/ha for the conditions of region. In a second experiment mixed silages of gliricídia and ground corn on fresh weight base, in the proportions of 100/0; 94/6; 88/12; 82/18; 76/24, and 70/30 were tested in 10 cm diameter and 30 cm long experimental silos for the parameters of: total dry matter (TDM), ether extract (EE), mineral matter (MM), acid detergent fiber (ADF) and neutral detergent fiber (NDF), crude protein (CP), pH, lactic acid and ammonia nitrogen (NH3-N). The addition of corn changed the chemical composition of the silage fermentation parameters, except for ammonia nitrogen. It is concluded that according with results found for the parameters evaluated in this study, it is not recommended the addition of ground corn silage gliricídia.